Nationalist Attitude towards the Main Character in the Film Chǎng Jīn Hú (长津湖) by Huángjiàn Xīn - Marthin, Andi; Erwani, Intan (Journal of Language Development and Linguistics, 2023)
This research aims to describe the nationalist attitude of the main character Wu Qianli in the film Chang Jin Hu (长津湖) and describe the supporting factors for the nationalist attitude of the character Wu Qianli in the film Chang Jin Hu. This research is motivated by literary works which have many nationalist values. The research method used in this research is descriptive-qualitative. The techniques used in collecting data are downloading films, watching films, screenshotting parts of films that have nationalist values. The results found from this research are that there are 3 attitudes of nationalism, namely having concern for the nation, having a movement to achieve independence, having the value of being willing to sacrifice and there are also supporting factors for morals in the nationalist attitude of the main character Wu Qianli, namely his own actions, conditions or situations and motives. . Therefore, this research has concrete data on the findings of a nationalistic attitude in the character Wu Qianli in the film Chang Jin Hu.